(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To compare the outcomes of rapid sequence intubation using video laryngoscopy versus direct laryngoscopy in anesthesia for emergency surgery. Results: The video laryngoscopy group has a significantly higher proportion of patients with Cormack-Lehane grade I-II compared to that of direct laryngoscopy group (98% vs. 78%, p < 0.05). The glottic exposure time was shorter in the video laryngoscopy group (9.3 ± 2.1 seconds vs. 12.9 ± 3.8 seconds, p < 0.05), and the mean number of intubation attempts was lower (1.02 vs. 1.18, p < 0.05). Conclusion: Rapid sequence intubation using video laryngoscopy offers several advantages over direct laryngoscopy, including reduced procedure time, a higher first-attempt success rate.